1991
DOI: 10.1128/jcm.29.11.2595-2598.1991
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high-level aminoglycoside resistance in enterococci other than Enterococcus faecalis

Abstract: The ability of six screening methods to detect high-level aminoglycoside resistance in enterococcal species other than Enterococcusfaecalis was investigated. The 85 Enterococcus isolates, which included 55 E. faecium, il E. gallinarum, 9 E. casseliflavus, 5E. raffinosus, 4E. avium, and 1 E. mundtii, were tested by using aminoglycoside-supplemented brain heart infusion agar (BHI), Remel EF Synergy Quad plates, high-content aminoglycoside diffusion disks, standard (prepared in-house) microdilution panels, Pasco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
3
16
1
1
Order By: Relevance
“…Studies have shown that prolonged incubation does not have a beneficial effect (30), but there have been reports demonstrating significant improvement of test sensitivity for the detection of HLAR (25,36). In our current study, prolonging the incubation to 48 h increased the detection rate by 6.2% for occurrences of resistance (CP phase).…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…Studies have shown that prolonged incubation does not have a beneficial effect (30), but there have been reports demonstrating significant improvement of test sensitivity for the detection of HLAR (25,36). In our current study, prolonging the incubation to 48 h increased the detection rate by 6.2% for occurrences of resistance (CP phase).…”
Section: Discussioncontrasting
confidence: 45%
“…Very major errors rarely occurred (1.0% for HLSR and 0.7% for HLGR). The most notable observation was the improved sensitivity of the PM-8 MicroScan panels for the detection of HLSR; earlier panels (25,30,36) detected isolates with HLSR at rates of only 41 to 90.2%. Reformulation of the panels with a modified basal broth appears to have enhanced the growth of enterococci resulting in improved test accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations